Microsatellite stable metastatic colorectal cancer without liver metastasis may be preferred population for regorafenib or fruquintinib plus sintilimab as third-line or above therapy:A real-world study - Nie, Caiyun; Lv, Huifang; Chen, Beibei; Xu, Weifeng; Wang, Jianzheng; Liu, Yingjun; Wang, Saiqi; Zhao, Jing; He, Yunduan; Chen, Xiaobing (Frontiers in Oncology, 2022)
Objectives The antitumor activity of nivolumab plus regorafenib in colorectal cancer from a phase Ib REGONIVO study is encouraging. The present study was conducted to evaluate the efficacy and safety of regorafenib or fruquintinib plus sintilimab as third-line or above therapy in patients with microsatellite stable (MSS) metastatic colorectal cancer. Methods Patients with MSS metastatic colorectal cancer who have failed from prior treatment and received regorafenib or fruquintinib plus sintilimab as third-line or above therapy from January 2019 to December 2020 were prospectively analyzed based on real-world clinical practice. The primary end point was progression free survival (PFS). Secondary end points included objective response rate (ORR), disease control rate (DCR), overall survival (OS), and safety. Results 42 patients received regorafenib plus sintilimab(RS), and the other 30 patients received fruquintinib plus sintilimab(FS). In the general population, the ORR and DCR were 13.9% and 70.8%, and the median PFS and OS was 4.2(95% CI=2.9-5.5) and 10.5 (95% CI=8.6-12.4) months, respectively. There were no statistically significant differences between RS and FS group in PFS (3.5(2.2-4.8) vs. 5.5(3.5-7.5) months, P=0.434) and OS (11.0(7.0-15.0) vs. 10.5(3.8-17.2) months, P=0.486). Subgroup analysis suggested that patients without liver metastasis responded well to this combination regimen (ORR: 21.4% vs. 9.1%) and obtained better OS (26(8.8-43.2) vs. 10.0(7.4-12.6) months, P=0.016). The incidence of Grade 3-4 adverse events (AEs) was 15.3% and the toxicities were generally tolerable and manageable. Conclusions Regorafenib or fruquintinib plus sintilimab as third-line or above therapy provide a feasible treatment regimen for MSS metastatic colorectal cancer with tolerated toxicity. Patients without liver metastasis may be the preferred population for this combination regimen.